Repeat Upper Gastrointestinal Endoscopy in Patients with Functional Dyspepsia: Yield, Findings, and Predictors of Positive Findings - Supot Pongprasobchai; Natta Asanaleykha; Pongchirat Tantayakom (Gastroenterology Research and Practice)
Background. No guideline on repeat esophagogastroduodenoscopy (EGD) in functional dyspepsia (FD) exists. This study aimed to define yield, findings, and predictors of positive findings on repeat EGD in FD. Methods. FD patients who underwent at least 2 EGDs during October 2005 to November 2011 were enrolled and reviewed. Yield and findings were analyzed and univariate and multivariate analyses were performed to identify predictors of positive repeat EGD. Results. The median time to repeat EGD was 34 months. Among 146 patients, 115 patients (79%) had negative and 31 (21%) had positive repeat EGD, including erosive gastritis (13.0%), peptic ulcer (7.5%), reflux esophagitis (1.4%), and Barrett’s esophagus (0.7%). Four independent predictors of positive repeat EGD were smoking (HR 3.88, 95% CI 1.31–11.51, P=0.015), hypertension (HR 2.96, 95% CI 1.38–6.36, P=0.050), history of malignancies (HR 3.65, 95% CI 1.16–11.46, P=0.027), and antiplatelets or NSAIDs used within 4 weeks (HR 4.10, 95% CI 1.13–14.90, P=0.032), while alarm features or failure to treatment did not predict positive repeat EGD.  Conclusion. Yield of repeat EGD in FD was substantially low, all findings were acid-related disorders, and there was no malignancy. Smoking, hypertension, history of malignancies, and antiplatelets/NSAIDs use associated with positive repeat EGD.